2009
DOI: 10.1016/s0924-9338(09)70777-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of placebo Effect in Therapy of Generalized Anxiety Disorder

Abstract: Studying of placebo response in patients with Generalized Anxiety Disorder (GAD) was the aim of research. 90 patients (68 female, 22 male, mean age of 33 years) were studied. All patients accepted inactive placebo (P) within 7 days and then - Alprazolam (A) in a dose of 1-3 mg per day within 4 weeks. Efficacy of treatment was estimated weekly by the HAM-A scale. After week of placebo reception, patients with HAM-A score < 9 made group of remission (R), with ≥50% HAM-A reduction - placebo responders group (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In anxiety disorders, an appreciable proportion of patients has been shown to respond favorably to placebo treatment [ 25 ]. This is also a known issue in placebo-controlled trials in the indication, and placebo response rates have been shown to even rise during the last decades [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In anxiety disorders, an appreciable proportion of patients has been shown to respond favorably to placebo treatment [ 25 ]. This is also a known issue in placebo-controlled trials in the indication, and placebo response rates have been shown to even rise during the last decades [ 51 ].…”
Section: Discussionmentioning
confidence: 99%